Chemical Characteristics of Coal Gangue as Filter Material in Simulated Coal Mine Goaf - Li, Xuejin; Wang, Hao; Liu, Bo (Asian Journal of Chemistry, 2013)
In this research, coal gangue was used as the main filler to deal with mine water in the simulated coal mine goaf, its filtering effect and mechanism were analyzed, and the filling characteristics were also analyzed and tested. The results showed that the gangue exhibited good removal characteristics for turbidity, iron and manganese of the mine water. In addition, the pollutants in the water in simulated goaf were removed by filtration, precipitation, adsorption and biochemical effects.